Do Not Cut Off Your Tail: A Mega-Analysis of Responses to Auditory Perturbation Experiments. - Miller, Hilary E.; Kearney, Elaine; Nieto-Castañón, Alfonso; Falsini, Riccardo; Abur, Defne; Acosta, Alexander; Chao, Sara-Ching; Dahl, Kimberly L.; Franken, Matthias; Heller Murray, Elizabeth S.; Mollaei, Fatemeh; Niziolek, Caroline A.; et al. (Journal of Speech, Language & Hearing Research, 2023)
Purpose: The practice of removing “following” responses from speech perturbation analyses is increasingly common, despite no clear evidence as to whether these responses represent a unique response type. This study aimed to determine if the distribution of responses to auditory perturbation paradigms represents a bimodal distribution, consisting of two distinct response types, or a unimodal distribution. Method: This mega-analysis pooled data from 22 previous studies to examine the distribution and magnitude of responses to auditory perturbations across four tasks: adaptive pitch, adaptive formant, reflexive pitch, and reflexive formant. Data included at least 150 unique participants for each task, with studies comprising younger adult, older adult, and Parkinson’s disease populations. A Silverman’s unimodality test followed by a smoothed bootstrap resampling technique was performed for each task to evaluate the number of modes in each distribution. Wilcoxon signed-ranks tests were also performed for each distribution to confirm significant compensation in response to the perturbation. Results: Modality analyses were not significant (p > .05) for any group or task, indicating unimodal distributions. Our analyses also confirmed compensatory reflexive responses to pitch and formant perturbations across all groups, as well as adaptive responses to sustained formant perturbations. However, analyses of sustained pitch perturbations only revealed evidence of adaptation in studies with younger adults. Conclusion: The demonstration of a clear unimodal distribution across all tasks suggests that following responses do not represent a distinct response pattern, but rather the tail of a unimodal distribution.